Alpha-amylase 1A copy number variants and the association with memory performance and Alzheimer’s dementia - Byman, Elin; Nägga, Katarina; Gustavsson, Anna-Märta; Andersson-Assarsson, Johanna; Hansson, Oskar; Sonestedt, Emily; Wennström, Malin (Alzheimer's research & therapy, 2020)
Background Previous studies have shown that copy number variation (CNV) in the alpha (α)-amylase gene ( AMY1A ) is associated with body mass index, insulin resistance, and blood glucose levels, factors also shown to increase the risk of Alzheimer’s dementia (AD). We have previously demonstrated the presence of α-amylase in healthy neuronal dendritic spines and a reduction of the same in AD patients. In the current study, we investigate the relationship between AMY1A copy number and AD, memory performance, and brain α-amylase activity. Methods and materials The association between AMY1A copy number and development of AD was analyzed in 5422 individuals (mean age at baseline 57.5 ± 5.9, females 58.2%) from the Malmö diet and cancer study genotyped for AMY1A copy number, whereof 247 where diagnosed with AD during a mean follow-up of 20 years. Associations between AMY1A copy number and cognitive performance where analyzed in 791 individuals (mean age at baseline 54.7 ± 6.3, females 63%), who performed Montreal Cognitive Assessment (MoCA) test. Correlation analysis between α-amylase activity or α-amylase gene expression and AMY1A copy number in post-mortem hippocampal tissue from on demented controls ( n = 8) and AD patients ( n = 10) was also performed. Results Individuals with very high ( ≥10) AMY1A copy number had a significantly lower hazard ratio of AD (HR = 0.62, 95% CI 0.41–0.94) and performed significantly better on MoCA delayed word recall test, compared to the reference group with AMY1A copy number 6. A trend to lower hazard ratio of AD was also found among individuals with low AMY1A copy number (1–5) (HR = 0.74, 95% CI 0.53–1.02). A tendency towards a positive correlation between brain α-amylase activity and AMY1A copy number was found, and females showed higher brain α-amylase activity compared to males. Conclusion Our study suggests that the degree of α-amylase activity in the brain is affected by AMY1A copy number and gender, in addition to AD pathology. The study further suggests that very high AMY1A copy number is associated with a decreased hazard ratio of AD and we speculate that this effect is mediated via a beneficial impact of AMY1A copy number on episodic memory performance.